Postoperative rehabilitation after total knee joint replacement - Vavro, Michal; Kollárová, Lívia; Szabó, Dávid; Libová, Ľubica (Magyar Gerontológia, 2021)
Objective:The pilot study objective was to evaluate the effect of comprehensive post-operative physiotherapeutic treatment on the selected physiotherapeutic parameters as well as patients’ quality of life after a total knee joint replacement surgery.Results:Thirty patients after total knee joint arthroplasty were enrolled into the pilot study. After completing the physiotherapeutic processes, we have observed among the patients who underwent a total knee replacement surgery, a significant increase in muscle strength as with the flexors as well as the extensors (p = 0.001), improvement in their range of motion in knee joint flexion, in comparison to its range before treatment (p = 0.001), knee pain reduction (p = 0.001) and post-operative swelling (p